Cenotaphe Bleu: A Fictional Monument - Akbar, Muhammad (JURNAL RUPA, 2024)
Cenotaphe Bleu is a research-based artwork that integrates motion-image creation with socio-political analysis through the depiction of a fictional monument, using the obelisk form as a symbol of Western colonial authority imposed upon colonized lands. The obelisk’s visual and cultural distance from local everyday life is intentionally constructed to emphasize the disconnection between the lived realities of the public and the utopian promises projected by the state promises that ultimately manifest as fictional narratives imposed upon society. The work critiques the state’s perspective, which mirrors the colonial gaze: projecting ideals onto its citizens without engaging their actual experiences. The visual presentation is developed through cinematographic techniques that use continuous camera movement to construct a spatial illusion, reflecting urban decay and social deterioration in relation to neglected monumental architecture. The chosen medium is 3D digital animation perceived as fabricated realism, and intaglio printmaking evoking the texture of archival documentation are deliberately juxtaposed to convey conflicting perceptions of truth, mirroring the contradictions in Bandung’s urban infrastructure and the unfulfilled narratives of state-led development.